2018
DOI: 10.1111/fcp.12355
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin attenuates homocysteine‐induced injury in human umbilical vein endothelial cells

Abstract: Homocysteine (Hcy) is a major risk factor for vascular disease and is closely associated with endothelial dysfunction. Melatonin is a neurohormone that is mostly produced by the pineal gland. Studies have reported that melatonin exhibits neuroprotective effects in several neurodegenerative disorders. The aim of the current study was to investigate the possible protective effect of melatonin against Hcy-induced endothelial cell apoptosis in human umbilical vein endothelial cells (HUVECs) and to explore the unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…MDA is one of the toxic products of free radical‐mediated lipid peroxidation and is a sensitive marker of oxidative stress and lipid peroxidation . Our results demonstrated that myricetin decreased lipid peroxidation in HUVECs in high glucose condition.…”
Section: Discussionsupporting
confidence: 55%
“…MDA is one of the toxic products of free radical‐mediated lipid peroxidation and is a sensitive marker of oxidative stress and lipid peroxidation . Our results demonstrated that myricetin decreased lipid peroxidation in HUVECs in high glucose condition.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, the total antioxidant power was significantly attenuated in H9C2 cardiac cells treated with Hcy [ 69 ]. Homocysteine-induced decreases in antioxidant defense were documented in vascular injury [ 4 , 70 , 71 , 72 , 73 ]. Studies on aorta have shown decreased expression of thioredoxin (Trx) and peroxiredoxin (Prx) [ 74 ].…”
Section: Homocysteine and Mitochondrial Oxidative Stressmentioning
confidence: 99%
“…Cells can protect themselves against oxidative stress-induced cell death through their internal antioxidant defense systems. The best known antioxidant defense systems are superoxide dismutase (SOD), catalase (CAT), and GSH (Aminzadeh and Mehrzadi, 2018b; He et al, 2017). In present study, Pb decreased cardiac TAP.…”
Section: Discussionmentioning
confidence: 99%